1999
DOI: 10.1200/jco.1999.17.1.371
|View full text |Cite
|
Sign up to set email alerts
|

Can 40 Seconds of Compassion Reduce Patient Anxiety?

Abstract: The enhanced compassion segment was short, simple, and effective in decreasing viewers' anxiety. Further research is needed to translate these findings to the clinical setting, where reducing patient anxiety is a therapeutic goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
341
1
12

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(383 citation statements)
references
References 37 publications
10
341
1
12
Order By: Relevance
“…For example, the Shared Decision-Making skills when applied in a context of communication about clinical trials have been showed to improve patient attitudes toward trial participation [63]. Establishing the consultation framework skills, such as inviting the patient's agenda in the right way, has been shown to eliminate unmet concerns [64] while empathic communication skills reduce patient anxiety [65].…”
Section: Mskcc Comskil Training Programmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Shared Decision-Making skills when applied in a context of communication about clinical trials have been showed to improve patient attitudes toward trial participation [63]. Establishing the consultation framework skills, such as inviting the patient's agenda in the right way, has been shown to eliminate unmet concerns [64] while empathic communication skills reduce patient anxiety [65].…”
Section: Mskcc Comskil Training Programmentioning
confidence: 99%
“…A coding manual was developed that operationalized each of the skills, further providing examples of when a particular skill should or should not be coded. 1 The first and fourth authors worked as coders on this project. They began by discussing 10% of the video recordings to further refine the coding system and work toward achieving inter-coder reliability.…”
Section: Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of cancer patients with anxiety disorders by standardised psychiatric criteria, mean STAI-S was 44.4, in contrast to 36 in those with normal levels of anxiety (Stark et al, 2002). The measure has been used for 30 years, with cancer patients, and has demonstrated factor structure and sensitivity to change (Spielberger, 1983;Fogarty et al, 1999).…”
Section: Questionnaires and Measuresmentioning
confidence: 99%
“…When clinicians acknowledge patients' emotions and invite discussion, they give them the opportunity to convey their concerns. Patients whose physicians are empathic and invite discussion disclose more concerns [36] and, as a result, have lower levels of distress [20,45,49].…”
Section: Introductionmentioning
confidence: 99%